2021
DOI: 10.1111/1462-2920.15296
|View full text |Cite
|
Sign up to set email alerts
|

From macro to micro: a combined bioluminescence‐fluorescence approach to monitor bacterial localization

Abstract: Bacterial bioluminescence is widely used to study the spatiotemporal dynamics of bacterial populations and gene expression in vivo at a population level but cannot easily be used to study bacterial activity at the level of individual cells. In this study, we describe the development of a new library of mini-Tn7-lux and lux::eyfp reporter constructs that provide a wide range of lux expression levels, and which combine the advantages of both bacterial bioluminescence and fluorescent proteins to bridge the gap be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Colony‐PCR was performed with primers OXRS_F4 and OXRS_R4 (Table S1) to validate the assembly. The lux operon, under the constitutive nptII promoter, was amplified with primers OXRS_F5 and OXRS_R5 (Table S1) from pRS p nptII ::lux (Soldan et al ., 2020). The PCR product was ligated into Sma I‐digested pRS01, generating plasmid pRS02.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colony‐PCR was performed with primers OXRS_F4 and OXRS_R4 (Table S1) to validate the assembly. The lux operon, under the constitutive nptII promoter, was amplified with primers OXRS_F5 and OXRS_R5 (Table S1) from pRS p nptII ::lux (Soldan et al ., 2020). The PCR product was ligated into Sma I‐digested pRS01, generating plasmid pRS02.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pRS02 was sequenced with primers OXRS_F4 and OXRS_R4 (Table S1) to validate the assembly. The λT0 terminator was amplified with primers OXRS_F6 and OXRS_R6 (Table S1) from pRS p nptII ::lux‐p A1/04/03 ::eYFP (Soldan et al ., 2020), and ligated into Sma I‐digested pRS02. The resulting plasmid contains pgl , p nptII ::lux operon with the λT0 terminator and ORF1 of picA .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study generated bioluminescent and fluorescent Pseudomonas syringae pv. phaseolicola [ 34 ]. The bioluminescence enabled detection of the bacteria at the leaf scale in a dedicated imaging chamber.…”
Section: Signs Symptoms and Sensorsmentioning
confidence: 99%
“…AttTn 7 is located downstream of the glmS gene, which encodes an essential glucosamine-fructose-6-phosphate aminotransferase ( Peters and Craig, 2001 ) and is found across bacterial phyla, including Proteobacteria, Firmicutes, and Bacteroidetes ( Wiles et al., 2018 ). Previous reports have shown that Tn 7 is active in the genera Pseudomonas , Xanthomonas , Rhizobium , Ralstonia , Burkholderia , Erwinia , Pectobacterium , and Pantoea to which many, if not all, phytopathogenic bacteria belong ( Choi et al., 2006 ; Choi and Schweizer, 2006 ; Jittawuttipoka et al., 2009 ; Kernell; Kovács et al., 2009 ; Kernell Burke et al., 2015 ; Romero-Jimenez et al., 2015 ; Zhang et al., 2021 ; Riccardo et al., 2021 ). Thus, Tn 7 -based genetic manipulation tools should be broadly applicable to studies on plant-bacterial pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%